The actions of the doctor in detecting a focal formation in the lung tissue - Elena V. Usacheva; Alina V. Palenykh; Nikita A. Usachev; Irina Yu. Botvinko (LLC "MEDIAFORMAT", 2024)
In order to provide timely and quality medical care to the population within the framework of improving the material base of medical organizations, many treatment and preventive care institutions have been equipped with modern X-ray equipment in the last three years. A large number of patients have been subjected to computed tomography of the chest organs, which has made it possible to detect asymptomatic pulmonary masses in a number of individuals. Taking into account the necessity of timely differential diagnostics of such masses and, first of all, in order to exclude malignant pulmonary neoplasms, the question arises what tactics should be followed by a primary care physician in case of detection of pulmonary neoplasms in a patient for the first time. The article presents a Clinical case demonstrating the detection of pulmonary neoplasm, which required active tactics of patient management, and presents tools, the use of which gives the doctor confidence in his actions for early diagnosis of malignant neoplasms.